Role conflicts in principalship its antecedents and relationships to administrative performance - Ruiz, Corazon Santos
This study attempted to ascertain the levels of role conflicts of principals and the determinants as well as its consequences to their administrative performance. The study was limited to the measurement of the levels of role conflicts among elementary school principals, the identification of some personal and organizational variables which may be related to the role conflicts and its relationships to the performance of public elementary school principals in the National Capital Region.
Keywords: Role conflict; Elementary school principals -- Philippines -- National Capital Region; School personnel management -- Philippines -- National Capital Region; Performance